2010
DOI: 10.1161/hypertensionaha.110.150102
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin Ameliorates Rat Cerebrovascular Remodeling During Hypertension via Inhibition of Volume-Regulated Chloride Channel

Abstract: Abstract-Statins have pleiotropic actions against the development of vascular remodeling and the incidence of ischemic stroke. Although previous studies have suggested that posttranslational modification of several proteins, such as Rho by mevalonate-derived isoprene groups, geranylgeranyl pyrophosphate or farnesyl pyrophosphate, underlie the pleiotropic effects of statins, the detailed mechanisms remain elusive. Recent growing evidence demonstrated that ClC-3 volume-regulated chloride channel plays an importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
54
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 39 publications
8
54
0
Order By: Relevance
“…Our previous study demonstrated that the expression of ClC-3 in basilar arteries was increased gradually with the development of cerebrovascular remodelling induced by hypertension (Liu et al, 2010), and a deficiency of ClC-3 attenuated cerebrovascular remodelling in DOCA-salt hypertension (Zheng et al, 2013). In the present study we showed that integrin β3 expression was positively correlated with ClC-3 expression in basilar arteries from 2K2C hypertensive rats, r = 0.641 (see Supporting Information Figure S3b).…”
Section: Integrin β3 Was Involved In Cerebrovascular Remodelling In Hsupporting
confidence: 69%
See 4 more Smart Citations
“…Our previous study demonstrated that the expression of ClC-3 in basilar arteries was increased gradually with the development of cerebrovascular remodelling induced by hypertension (Liu et al, 2010), and a deficiency of ClC-3 attenuated cerebrovascular remodelling in DOCA-salt hypertension (Zheng et al, 2013). In the present study we showed that integrin β3 expression was positively correlated with ClC-3 expression in basilar arteries from 2K2C hypertensive rats, r = 0.641 (see Supporting Information Figure S3b).…”
Section: Integrin β3 Was Involved In Cerebrovascular Remodelling In Hsupporting
confidence: 69%
“…Our previous studies showed that smooth muscle α-actin staining was increased time-dependently in basilar arteries from 2K2C hypertensive rats. The mean values of medial cross-sectional area (CSA) increased in the hypertensive group after 4 weeks post-operatively compared with those in corresponding control groups (Liu et al, 2010). The present study showed that integrin β3 expression was positively correlated with the medial CSA of the basilar artery from 2K2C hypertensive rats, r = 0.6025 ( Figure 1D).…”
Section: Integrin β3 Was Involved In Cerebrovascular Remodelling In Hsupporting
confidence: 51%
See 3 more Smart Citations